Design with part behaviors: behavior model, representation and applications - Roy, U.; Bharadwaj, B. (Computer aided design, 2002)
A part is primarily characterized by its ‘function(s)’. The function of the part is achieved through its ‘interactions’ with other parts in an assembly under a set of operating conditions. These ‘interactions’ constitute the ‘behavior’ of the part. The ‘part behavior’ is achieved through a set of spatial and design functional relationships between the interacting surfaces of the parts. The set of spatial and design functional relationships for a part constitutes the Part Function Model (PFM) of that part. In this paper, the nature and role of part ‘functions’ and ‘behaviors’ have been studied in the context of a product design system. The paper addresses the following issues: (i) relationship between function, behavior, and geometry of a part; (ii) importance of ‘part behavior’ over ‘part function’, and development of a ‘part behavior’ model; (iii) methodology for transforming the part behaviors into the PFM model of the part; (iv) product model framework for storing the PFM model information with an Object Oriented Programming (OOP) based CAD system (Concentra's Concept Modeller); (v) importance of the PFM model within the product development process; and (vi) application of the PFM model for generating various product specifications of the part. The prototype implementation of a Functional Design System for transforming part behaviors into different types of part specifications has also been presented in this paper.